Clinical study on wound healing properties of Nile tilapia fish skin as biological dressing in dogs - Khizer Ahmed Khan; Uzma Farid Durrani; Asim Khalid Mahmood; Muhammad Yasin Tipu; Amber Fatima; Hussain Ahmad Saeed; Abdul Karim Khalid; Tuba Shuja Ansari (PLoS ONE, 2025)
Frequency of clinical cases of dogs with massive skin losses is very high in urban areas of Pakistan following road accidents, sharp objects exposure and attack by other dog. These cases need intensive veterinary assistance for safe and speedy healing of wounds. Recently, skin of Nile tilapia fish (Oreochromis niloticus) is internationally gaining hype in medical field as biological dressing to boost dermatological reconstruction process. Nile tilapia skin is a recent research trend and a very limited research data is available on this topic for both human and animal subjects. This study was conducted at Department of Small Animal Clinical Sciences, University of Veterinary and Animal Sciences (UVAS), Lahore, Pakistan considering the wound healing promoter properties of Nile tilapia skin as a biological dressing for dogs with massive skin losses. Aim of this study was to evaluate Nile tilapia fish skin as wound healing promoter biological dressing following sutured and non-sutured application techniques. For this study 10 clinical cases of dogs were randomly selected as per set criteria and divided into groups A and B comprising 5 dogs each. Consent document was signed by each dog owner for volunteer participation in this study. Nile tilapia skin was collected from fresh subjects and treated with 10% povidone-iodine for 10-15 minutes to prepare biological dressing. In group A, biological dressing was sutured on wound (non-absorbable silk suture material) on the area with dermal loss. In group B, biological dressing was applied in a wrap manner on area of dermal loss without application of sutures. Wound healing was evaluated grossly and histologically on days 0, 7 and 14. Statistical analysis of comparison between groups A and B revealed that application of Nile tilapia skin derived biological dressing in wrap fashion results in fast and complication-free wound healing as compared to sutured tilapia biological dressing in dogs.